Bibliometric analysis of evolutionary trajectory and prospective directions of LAG-3 in cancer - Wang, Jin; Wang, Siying; Zhang, Yuting; Zhang, Wei (Frontiers in Immunology, 2024)
Objectives: Perform a bibliometric analysis on the role of LAG-3 in the domain of cancer, elucidate the prevailing areas of research, and visually depict the evolutionary trajectory and prospective directions of LAG-3 research over the past twenty-three decades.Between 2000 and 2023, a comprehensive review of scholarly articles pertaining to LAG-3 research in the context of cancer was carried out using the Web of Science Core Collection (WoSCC) database. Bibliometric analysis can be conducted by taking advantage of VOSviewer (version 1.6.16) and CiteSpace (version 6.2.R4). Create a network diagram to visually represent various authors, countries, and organizations while assessing the publishing years, journals, references, and keywords.In conclusion, 1841 records were identified and published in 587 publications. These records were authored by 12,849 individuals affiliated with 2491 institutes across 74 countries. There has been a substantial surge in publications subsequent to 2013. The USA, China, and Germany gave the majority of records, amounting to 69.69%. American institutions actively engage in collaboration with institutions located in other countries. Triebel, F., Vignali, Dario A.A., Workman, Creg J. Drake, Charles G., and Elkord, Eyad are highly regarded authors in their respective fields. However, it is worth noting that Triebel exhibits limited collaboration with other writers. The examination of the role of LAG-3 in cancer and its potential for use in clinical settings is a discernible trend, as seen by keyword analysis.The scientific interest in and attention towards LAG-3 has experienced a significant rise since 2013. The United States is leading the way, with China following closely behind. Promoting collaboration among writers, nations, and institutions with varied backgrounds is imperative. The discipline of immunotherapy is currently seeing ongoing progress. A thorough investigation of the distinctive cis ligand TCR-CD3 complex of LAG-3 and its signal transduction mechanism is necessary. Additionally, it is worthwhile to explore novel combinations of LAG-3 therapy.